H-Infinity Electronic Controller Fails for Integrated Delay in Aircrafts - Srikanth, Kavirayani (Journal of Electronic Design Engineering, 2023)
When the time delay is integrated into the dynamic system definition and the analysis of a complex dynamic system such as aircraft is carried out, it depicts that integrating the delay into the definition would be advantageous in evaluating the performance of the aircraft at a faster rate. It also stabilizes the plant at a faster rate when compared to classical control techniques applied on systems considering delay as a separate entity. An H-infinity controller is designed for the integrated system and analyzed as part of the studies that yielded interesting observations on the H-infinity limitations. The analysis of the system when compared to simple classical control techniques is vividly advantageous however when delays are integrated and critical delay impacts are not calculated, the chances for failure of a dynamic system control predominantly increase owing to varied complex governing equations which otherwise would be approximated with linear models.